Platelet Rich Plasma in Arthroscopic Rotator Cuff Repair: Clinical and Radiological Results of A Prospective RCT Study at 10-Year Follow-Up. Issue 7 (30th July 2021) - Randelli, Pietro; Stoppani, Carlo Alberto; Nocerino, Elisabetta; Menon, Alessandra; Compagnoni, Riccardo
Objectives: Despite the technical advancement in arthroscopic rotator cuff repair, inadequate healing or retear of the repaired rotator cuff frequently occurs. The use of biological factors in the surgical treatment has been proved to be effective to enhance tendon healing in the post-operative period. The aim of the study is to compare clinical and radiological outcomes of arthroscopic rotator cuff repair with or without the addition of platelet-rich plasma (PRP) at 10-year follow-up. Methods: Of 53 patients recruited in the study, and randomly divided into two groups (PRP=26; control=27), 38 were re-evaluated at least 10 years after the index procedure. The clinical evaluation was carried out through: University of California at Los Angeles (UCLA) Shoulder Score, Visual Analogue Scale (VAS), Simple Shoulder Test (SST), Constant-Murley Score (CMS), Single Assessment Numerical Evaluation (SANE), American Shoulder and Elbow Surgeons (ASES) and isometric strength in abduction and external rotation. Musculoskeletal ultrasound had been used to evaluate the integrity of the repaired cuff. Results: A number of 38 (71%) patients (PRP=17; control=21) with a median age of 71 [64.75-76.50] years have been evaluated. Satisfaction at follow-up is high (90%), without statistically significant difference between the two groups. We report good and excellent clinical results in both groups (PRP vs control): CMS (81.62 [72.47-85.75] vs 77.97 [69.52-82.55] points), UCLA (34 [29.00-35.00] vs 33 [29.00-35.00] points), VAS (0.34 [0.00-1.85] vs 0.70 [0.00-2.45] cm), ASES (100.00 [94.17-100.00] vs 93.33 [68.33-100.00] points), SANE (100 [80-100] vs 80 [70-90] points), SST (12.00 [11.00-12.00] vs 12.00 [9.00-12.00] points), shoulder abduction strength (3.92 ± 2.30 vs 3.20 [1.72-4.65] kg), shoulder external rotation strength (5.31 ± 2.77 vs 4.36 ± 2.05 kg). It was not possible to find a statistically significant difference for the variables analysed, except for few subjective variables (ASES, SANE). On average, 37% of the operated patients had a re-rupture at the ultrasound examination, with no significant difference between the two groups (p=1.00). Compared with the previous radiological control at the 2-year follow-up, new retears occurred in 6% of the patients that received PRP treatment, whereas in the control group the percentage raises to 14% (p=0.61). Conclusions: The clinical and radiological outcomes at the 10-year follow-up show a substantial uniformity of results between the two groups. The clinical differences that had been observed at 2-year follow-up disappeared at long term. A reduction in retear rate is observed at US evaluation in the PRP group at 10 years follow-up and this trend needs to be further analyzed. Patients' satisfaction is still high 10 years after surgical treatment, in both groups.